PENGARUH KONSENTRASI EKSTRAK BUAH MAHKOTA DEWA (Phaleria macrocarpa (Scheff.) Boerl) TERHADAP PENGHAMBATAN ADHESI BAKTERI Streptococcus sanguinis (Kajian In Vitro) - , AYU FRESNO ARGADIANTI, drg. Ruslin, M.Kes, Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Bacterial adhesion is a primary requirement in the formation of dental plaque and development of caries. Streptococcus sanguinis, one of the initial bacteria appeared on adhesion process, equipped with ability to produce sIgA protease and extracellular glucans to adhere to tooth surface. This study was aimed on determining effect of Phaleria macrocarpa (Scheff.) Boerl) fruit extract on inhibiting Streptococcus sanguinis adherence. Phaleria macrocarpa (Scheff.) Boerl) fruit was extracted by maceration method using ethanol 96% as solvent then diluted by aquadest to get 25%, 27.5% and 30% concentrations. Streptococcus sanguinis was isolated from agar slant from Balai Laboratorium Kesehatan Yogyakarta, incubated in BHI with sucrose added with various concentrations of Phaleria macrocarpa (Scheff.) Boerl fruit extract. Aquadest as negative control and chlorhexidine 0.12% as positive control. The adherence test was quantified spectrophotometerically at 600 nm. This study showed mean difference on all groups with one way ANOVA result 0.000 (p<0.05). LSD Post Hoc test showed that the extract with 27.5% and 30% concentration had similar ability with chlorhexidine 0.12% to inhibit Streptococcus sanguinis adherence. Hence, this study reveals Phaleria macrocarpa (Scheff.) Boerl fruit extract has inhibition effect on adherence of Streptococcus sanguinis.